Řízení podniku speciálních stavebních prací v současné hospodářské situaci - Šumichrastová, Ivana (Vysoké učení technické v Brně. Fakulta stavební, 2016)
Cielom prace je analyza nedavnej i sucasnej situacie v hospodarstve SR, ako aj oblasti stavebneho priemyslu. V kontexte vonkajsich a vnutornych vplyvov sa dalej rozobera hospodarenie podniku specialnych stavebnych prac a jeho casti. Detailnejsi rozbor sa opiera o vysledky financnej analyzy. Zamerom diplomovej prace je zistit aky dosah mali tieto udalosti na konkretny podnik a nasledny navrh opatreni, ktore by prispeli k jeho odolnosti voci konkurencii, pripadne pomohli prekonat potencionalne dalsie krizove obdobie.

The aim of the work is an analysis of recent and present economic situation and also situation in construction in Slovak Republic. It deals with the economy of a particular company, which specialises in the field of construction works, in the context of outside and inside influences. A more detailed examination relies on the results of a financial analysis. The aim of the thesis is to find out what impact these events have on a specific company and to suggest solutions that would contribute to its resilience to its competition or to help overcome the next potential crisis.
Management of Company focused on special Construction works in curent economic situation
Keywords: Hospodarstvo SR; stavebnictvo; kriza; financna analyza; pomerove ukazovatele; diverzifikacia podnikatelskej cinnosti; specialne stavebne prace.; Economic situation of SR; construction; crisis; financial analysis; financial ratios; diversification of business activity; special construcion works.